Arrheton - Unspeakable in the Greek Mystery Cults - Bielawski, Krzysztof (Filozofia Chrześcijańska, 2016)
The paper presents meaning and use of two technical words important for understanding and interpretation of the ancient mystery cults and mystical experience of ancient Greeks: arrheton and aporrheton – “unspeakable” and “forbidden”. The introduction contains general guidelines of so called “Greek religion” with its focus on performance and ritual and describes the rôle of mystery cults in the frame of this adogmatic religious system. The paper explains lexicography of the crucial terms, including etymology, ancient vocabularies and grammar and then turns to the catalogue and interpretation of the most important literary and epigraphical evidence on the use and meaning of arrheton in the Greek culture. The catalogue contains Aristotle, Xenophon, Herodotus, Aristophanes, Euripides, Sophocles, Apuleius and Derveni Papyrus as well as early Christian writers.